Deciphering Epitranscriptome: Modification of mRNA Bases Provides a New Perspective for Post-transcriptional Regulation of Gene Expression - Kumar, Suresh; Mohapatra, Trilochan (Frontiers in Cell and Developmental Biology, 2021)
Gene regulation depends on dynamic and reversibly modifiable biological and chemical information in the epigenome/epitranscriptome. Accumulating evidence suggests that messenger RNAs (mRNAs) are generated in flashing bursts in the cells in a precisely regulated manner. However, the different aspects of the underlying mechanisms are not fully understood. Cellular RNAs are post-transcriptionally modified at the base level, which alters the metabolism of mRNA. The current understanding of epitranscriptome in the animal system is far ahead of that in plants. The accumulating evidence indicates that the epitranscriptomic changes play vital roles in developmental processes and stress responses in plants. Despite being widely detected and having well-known functions in ribosomal-RNAs and transfer-RNAs, different aspects of base modifications in mRNAs are far from adequate to assign the molecular basis and functions of the epitranscriptomic changes. Recent advances in the chemogenetic RNA-labelling and high-throughput next-generation sequencing techniques have enabled functional analysis of the epitranscriptomic modifications to reveal their roles in mRNA biology. Mapping of the common mRNA modifications, including N6-methyladenosine (m6A), 5-methylcytidine (m5C), and pseudouridine, has enabled the identification of other types of modifications, such as N1-methyladenosine. Methylation of bases in a transcript dynamically regulates the processing, cellular export, translation, and stability of the mRNA; thereby influence the important biological and physiological processes. Here, we summarise the findings in the field of mRNA base modifications with special emphasis on m6A, m5C, and their roles in plant growth, development, and stress tolerance, which provides a new perspective for the regulation of gene expression through post-transcriptional modification. This review also presents the complementary roles of epigenome and epitranscriptome in the regulation of gene expression, addresses some of the scientific and technical issues in epitranscriptomic study, put forward the viewpoints to resolve the issues, and discusses the future perspectives of the research in this area.